Inventarisasi Selaginellaceae di Hutan Lindung Aek Nauli Parapat Sumatera Utara - Jamilah Nasution; Ida Fauziah; Ferdinand Susilo (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2017)
This research aims to determine the types of Selaginella in the field and to know the existence of species within a community. This study was conducted by collecting specimens from the field followed by inventory and identification of Selaginella species, as well as recording environmental conditions.The results of this study obtained 5 types of Selaginella: Selaginella intermedia, Selaginella kityyae, Selaginella longariastata, Selaginella ornata and Selaginella willdenovii. Based on their habitat Selaginella intermedia, Selaginella kityyae, Selaginella longariastata and Selaginella willdenovii found in field, have a terrestrial habitus spread, whereas Selaginella ornata is an upright epilithic terrestrial, with each species found mostly in clusters and dominate in an area.